Studi Keragaman Struktur Morfologi dan Anatomi Petiole (Tangkai Daun) Dari Berbagai Kultivar Pisang Kepok (Musa Paradisiaca L.) - Galuh putri anjasmara; Eti Ernawiati; Gina Dania Pratami; Endah Setyaningrum (Jurnal Penelitian Pertanian Terapan, 2020)
Kepok bananas are one type of banana that is found and used in Indonesia. These bananas contain high nutritional value so they are suitable for use as food ingredients. This study aims to determine the anatomical structure and morphology of petiole from various banana kepok cultivars. These cultivars are: kepok abu, batu, kapas, kuning, Libanon, and Manado. However, Kepok Libanon cannot be found in the previous collection area. The research was conducted in December 2018 to January 2019. The taking of plant samples using the method of exploration and observation of anatomical structures using fresh preparations across the incision and the results were analyzed descriptively. The observation of the structure of morphology of petiole is the largest petiole diameter, namely kepok kapas while the smallest is kepok batu. Kepok batu is the only one that has a canal leaf shape overlaps whileÂ  kepokÂ  abu, kapas, kuning, and manado have the leaf shape of a curved canal inside. The fifth color of the kepok banana cultivar is the same which is green. Kepok abu have blackish brown spots while kepok batu, kapas, kuning, and manado have brown spots. The anatomical structure of the petiole includes the xylem diameter, transport tissue, support tissue, basic tissue, and protector tissue. Kepok kapas has the largest xylem diameter while kepok kuning has the smallest xylem diameter. Five kepok banana cultivars, has xylem and phloem transport tissue were clearly seen by the sclerenchyma sheath. Epidermal, parenchymal, and sclerenchymal tissue were clearly seen in the five cultivars.